النظام القانوني لميزانية البلدية في الجزائر - بن سديرة جلول (My University, 2025)
تعتبر ميزانية البلدية أداة هامة وضرورية الاضطلاع البلدية بوظيفتها الأساسية المتمثلة في مجموعة كبيرة من المهام، ترتكز كلها على العمل من أجل تحسين الإطار المعيشي المواطن، وهي العملية التي تتم في هذا الإطار عبر مراحل إجرائية وضوابط قانونية، لها خصوصيات مختلفة ومتميزة في ذات الوقت، مستمدة من بنية الهيكل الإداري لهذه البلديات بعد القرار المالي الجانب القانوني المهم والحلقة الجوهرية باعتباره كأحد أهم الأعمال التي تتخذ داخل المجالس المنتخبة على مستوى البلديات، إذ بموجبه يعطى الرؤساء المجالس الشعبية البلدية بعد استكمال إجراء المصادقة عليه من طرف السلطة الوصية الرخصة المالية التي تخول لهم ممارسة سلطة التنفيذ، بما يمكنهم من إدارة مداخيل البلديات التي يمثلونها وفي ذات الوقت الأمر بصرف نفقاتها يتطلب تجسيد هذا العمل على أرض الواقع، مجموعة من المنطلقات القانونية تبدأ بما يسمى بالمرحلة السابقة على اتخاذ القرار المالي البلدي، باعتبارها مرحلة مهمة تتضمن المدخلات الرئيسية المتمثلة في عرض أساسيات الإعداد والتحضير، وذلك من أجل رصد الإمكانيات المالية وضبط الحاجات الإتفاقية، وباعتماد القرار المالي تأتي مرحلة تنفيذ المخرجات، أين يتدخل فيها رؤساء المجالس الشعبية البلدية بصفتهم كأمرين بالصرف وأمناء خزائن البلديات بصفتهم كمحاسبين عموميين، يليهما مرحلة الرقابة التي تمارسها مصالح وهيئات مختلفة، الهدف منها هو التحقق والتحقيق في مشروعية العمليات المالية المزمع إنجازها أو التي تم إنجازها. إن مراحل إعداد وتحضير وتنفيذ ميزانية البلدية، والرقابة الممارسة عليها غير كافية، ما لم يتضح بعد القرار المالي البلدي من حيث ارتباطه بالإستراتيجية التنموية للدولة، والأداة المعتمدة في ذلك، ومن ثم تشخيص الوضع المالي للبلديات من أجل تقديم الإصلاحات المناسبة في مقدمتها ضرورة إرساء نظام قانوني يستقطب تلك المنتخب البلدي الذي تجتمع فيه المقومات الجوهرية، وهي المستوى العلمي والخبرة المهنية والنزاهة، وذلك قبل المرور الأي إصلاح آخر The municipal budget constitutes an important and indispensable instrument enabling municipalities to carry out their fundamental function, which consists in performing a wide range of tasks primarily aimed at improving the living conditions of citizens. This process is carried out within a specific legal and procedural framework governed by various stages and legal controls, characterized by particular features derived from the administrative structure of municipalities. The financial decision represents the most significant legal aspect and a core element, as it is considered one of the most important acts adopted within elected municipal councils. By virtue of this decision, and after its approval by the supervisory authority, the Presidents of the Municipal People's Assemblies are granted a "financial authorization" that confers upon them the power of execution. This enables them to manage municipal revenues and, at the same time, to authorize and commit municipal expenditures. The practical implementation of this process requires a set of legal foundations, beginning with the so-called preliminary stage preceding the adoption of the municipal financial decision. This stage is of particular importance, as it includes the main inputs related to the presentation of preparation and planning fundamentals, with the aim of identifying financial capacities and determining expenditure needs. Following the adoption of the financial decision comes the execution phase, during which the Presidents of the Municipal People's Assemblies intervene in their capacity as authorizing officers, alongside municipal treasurers rets acting as public ace accountants. This phase is subsequently followed by the control stage, exercised by various services and bodies, whose purpose is to verify and ensure the legality of the financial operations intended to be carried out or already executed However, the stages of preparation, adoption, execution, and control of the municipal budget remain insufficient unless the municipal financial decision is clearly understood in terms of its connection to the State's development strategy and the instruments adopted to achieve it. This further requires an accurate diagnosis of the financial situation of municipalities in order to propose appropriate reforms, foremost among which is the necessity of establishing a legal framework capable of attracting a qualified municipal elected official who possesses the essential qualities of academic competence, professional experience, and integrity, prior to undertaking any other reform.
Keywords: ميزانية البلدية، القرار المالي البلدي، تنفيذ الميزانية، الرقابة المالية، التنمية المحلية، المنتخب البلدي، الإصلاح المالي.